Frequency and type of arrhythmia in Holter electrocardiogram in patients undergoing hemodialysis: Hemodialysis patients – arrhythmia - Yurdam, Ferhat Siyamend; Kış, Mehdi (Journal of Surgery and Medicine, 2023)
Background/Aim: It is known that approximately 40% of chronic hemodialysis patients die due to cardiac arrhythmia and cardiovascular reasons. Determining whether the hemodialysis procedure poses a risk for arrhythmia is important in terms of prognostic follow-up of the patients. Therefore, we aimed to determine the underlying arrhythmia frequency and types with 24-hour Holter electrocardiogram (ECG) in patients receiving hemodialysis with normal baseline electrocardiography between the hemodialysis periods. Methods: Between January 2018 and January 2022, 91 consecutive patients who received hemodialysis for chronic renal failure (CRF) and applied to the cardiology outpatient clinic with complaints of palpitation and sinus rhythm on ECG and evaluated with 24-hour rhythm Holter ECG were included in the study. Our study was designed as a retrospective cohort study. Results: The mean age of the patient population was 65.78 (11.92) years, the mean systolic blood pressure was 143.71 (24.88) mmHg, and the mean heart rate was 83.43 (15.85) beats/min. Hypertension (HT) (n=44, 48%) and coronary artery disease (n=34, 37%) were the most common comorbid diseases. The most common arrhythmias detected on Holter ECG were ventricular extrasystole (VES) (n=18, 19.8%) and paroxysmal AF (n=8, 8.8%). Non-sustained ventricular tachycardia was detected in two patients. Conclusion: Detecting arrhythmia in the interdialytic periods in patients receiving hemodialysis due to CRF is important for follow-up and treatment. Even if the baseline ECG is normal in hemodialysis patients with CRF, the frequency of the underlying arrhythmia that needs to be treated is high.